2018
DOI: 10.1002/brb3.1178
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for endovascular treatment in anterior circulation stroke: A systematic review and meta‐analysis

Abstract: BackgroundEndovascular treatment in patients with acute anterior circulation stroke could be performed under either conscious sedation (CS) or general anesthesia (GA). Although several studies have investigated the association between the clinical outcomes and the two anesthesia methods, consensus is lacking.MethodsPubMed and EMBASE searches were used to select full‐text articles comparing the effects of GA and CS on functional outcome and complications in patients with anterior circulation ischemic stroke. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, only for RCTs, GA was associated with improved functional outcomes. 33 In our initial analysis, GA showed lower good outcomes (OR, 0.564; 95% CI, 0.354-0.899). But, the funnel plot was slightly asymmetric, indicating possible publication bias.…”
Section: (2010)mentioning
confidence: 76%
See 2 more Smart Citations
“…However, only for RCTs, GA was associated with improved functional outcomes. 33 In our initial analysis, GA showed lower good outcomes (OR, 0.564; 95% CI, 0.354-0.899). But, the funnel plot was slightly asymmetric, indicating possible publication bias.…”
Section: (2010)mentioning
confidence: 76%
“…Regarding successful recanalization, anesthesia type did not affect outcomes in acute stroke patients who underwent mechanical thrombectomy only (OR, 0.831; 95% CI, 0.616–1.122). Li et al [ 33 ] investigated anesthesia effect on clinical outcomes in patients with anterior circulation stroke and reported inconsistent results. CS was related to improved outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our main finding is in line with several observational studies, [3][4][5][6][7][8][9][10][11][12][13][14]32,33 systematic reviews, and meta-analyses. [34][35][36][37][38][39][40][41] In particular, the 2 largest single studies to date, a meta-analysis of individual patient data from 1764 patients receiving EVT in RCTs by the HERMES (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) collaboration, and 2 registry cohort studies from Italy and Germany of EVT in acute stroke with 4429 and 5808 patients, respectively, showed a worse functional outcome after EVT under GA compared with non-GA. 32,33,36 Recently, GA versus conscious sedation versus local anesthesia alone were compared among 1376 patients in the MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) registry yielding best functional outcome with local anesthesia. 42 Five RCTs of limited size have compared outcomes after EVT with versus without GA: The AnStroke trial (Anesthesia During Stroke) reported no difference in 3 months mRS between GA and non-GA in 90 patients.…”
Section: Discussionmentioning
confidence: 99%